Mastering turbulence the essential capabilities of agile and resilient individuals, teams, and organizations - McCann, Joseph E. (Jossey-Bass business & management series., 2012)
"The essential capabilities organizations need to master turbulent changeRapid and disruptive change threatens the adaptive capacity of organizations, along with the individuals and teams leading them. Based upon over a decade of global research and consulting, Joseph E. McCann and John W. Selsky outline five capabilities highly agile and resilient systems must possess. They must be: Purposeful, Aware, Action-Oriented, Resourceful, and Networked. In addition the authors illustrate how these capabilities can be assessed across four levels--individuals, teams, organizations, and their business ecosystems. The goal is to develop these capabilities in tandem so that the individual, team, organization and ecosystem have High AR--not just greater agility or resiliency, but both high agility and high resiliency. The authors outline balanced development strategies for creating High AR that can be used to master turbulent environments for competitive advantage and sustained performance Includes cutting-edge concepts and examples that take readers from the latest advances in neuro-science and executive wellness to global supply chains and innovation strategy. Contains illustrative examples and vignettes from leading organizations including Mayo Clinic, Microsoft, Starbucks, Southwest Airlines, TECO Energy, Shell Oil, Walmart, and others Most important, McCann, and Selsky deliver a unique and practical perspective that helps organization leaders make sense of the dynamic world in which they operate"--